Neurological soft signs in children with attention deficit hyperactivity disorder: Their relationship to executive function and parental neurological soft signs. Issue 1 (30th July 2015) - Gong, Jingbo; Xie, Jingtao; Chen, Gui; Zhang, Yajie; Wang, Suhong
Abstract: The correlations between neurological soft signs (NSS) in children with attention deficit hyperactivity disorder (ADHD) and their executive function, symptoms of inattention, and hyperactivity–impulsivity and the NSS of their parents remain unclear. This study aimed to examine: (1) the prevalence of NSS in children with ADHD and their parents; (2) the correlation between the NSS of children with ADHD and the NSS of their parents; and (3) the correlation between the NSS of children with ADHD and their executive function and symptoms. NSS were assessed with the Cambridge Neurological Inventory (CNI) in 57 children with ADHD (and 80 parents) and 60 healthy children (and 75 parents). Executive function was measured with the Behavioral Rating Inventory of Executive Function (BRIEF). Children with ADHD and their parents had significantly higher NSS than normal children and their parents, respectively, and the NSS of children with ADHD were correlated more strongly with the NSS of their fathers than their mothers. No correlation was found between NSS and BRIEF executive function, but Disinhibition in children with ADHD was significantly correlated with hyperactivity–impulsivity symptoms. Paternal and maternal NSS provided different predictions for child NSS. It may be that NSS are more likely to be genetically transmitted by fathers. Highlights: Paternal and maternal NSS provided different predictions for child NSS. NSS are more likely to be genetically transmitted by fathers. Disinhibition of NSS was a significant independent determinant of symptom of hyperactivity–impulsivity.